Subjective oral health measures in caregivers of patients with autism spectrum disorder and down syndrome: a preliminary study (Bioscience Journal, 2023)
This study aimed to address the subjective oral health measures of caregivers of individuals with autism spectrum disorder (ASD) and Down syndrome. This cross-sectional study included 15 caregivers of individuals with ASD (n = 7) and Down syndrome (n = 8). Sociodemographic data, sense of coherence (SOC) (SOC-13 scale), social support (Social Support Scale [MOS-SSS]), oral health-related quality of life (OHRQoL) (OHIP-14), and self-rated oral health assessed on a 5-point Likert scale were collected. A descriptive analysis was performed in addition to correlation analyses (Spearman correlation coefficient). Most primary caregivers were parents of the individual (86.6%). The age of the caregivers ranged between 40 and 59 years (60%). Most caregivers have had 9 to 11 years of education (53.3%). Monthly family income was less than USD 186,28 for ASD caregivers (57.2%) and between USD 327,56 and USD 931,40 for Down syndrome caregivers (50%). Of the caregivers, 33.3% reported good oral health and 33.3% reported neither good nor bad. The average SOC score, social support and OHRQoL was 48.9, 69.3 and 10.9, respectively. The higher the family income, the better the OHRQoL (rs = -0.62, p = 0.014). SOC was correlated with the score of the emotional support domain (rs = 0.54, p = 0.039). It was concluded that caregivers had a strong SOC and high perceived support. Moreover, caregivers did not report a high impact on OHRQoL A better understanding of the caregivers’ protective and coping factors in caring for individuals with disabilities may better promote their quality of life.